Legal Analysis of Criminal Acts of Extortion and Threats Through Electronic Media - Andri, Andri; Asmi Hasibuan, Saiful (PT. Multidisciplinary Press Indonesia, 2024)
The rapid development of information technology has changed human life to be easier. This has caused changes in human life activities in various fields which have also directly influenced the birth of new criminal acts related to information technology. One of these crimes is extortion and threats through information technology which in principle are the same as conventional extortion and threats, the only difference is that the means are through information technology. The legal regulations used in criminal acts of extortion and threats through information technology are Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions